Sliding Mode Control for Four Wheels Electric Vehicle Drive. (2016) - Nasri, Abdelfatah; Gasbaoui, Brahim; Fayssal, Ben Mohammed
Abstract: In this research a novel control schema of four wheels drive (4WD) propulsion system control is presented. The present paper introduces novel studies of sliding mode control applied on four independent wheels electric vehicle systems. The proposed propulsion system consists of four Induction Motors (IM) that ensure the driving of back and front driving wheels. This vehicle uses an electronic differential for speeds reference computations of four wheels. The electronic differential system ensures the robust control of the vehicle behaviour on the road; it also allows controlling, independently, every driving wheel to turn at different speeds in any curve. The result obtained is satisfactory for our electric vehicle sliding mode control's simulated in Matlab Simulink environment. It shows the efficiency of the proposed control comparing with classical PI controller with no overshoot. The rising time is perfected with good disturbances rejections.